Neuraxial anaesthesia in a parturient with space occupying lesion in brain for caesarean section: Demystifying the myth - A case report with review - Abinaya Ramachandran; Sivakumar Segaran; Nikithamani; R V Ranjan (Wolters Kluwer Medknow Publications, 2022)
Pregnancy makes a patient undergo diverse physiological changes and predisposes them to many pathological disorders such as pre-eclampsia, eclampsia, cortical vein thrombosis, and pituitary apoplexy. Any intervention during pregnancy presents a unique challenge as it affects two individuals. Once diagnosed with a clinical condition, they are prone to further medical, obstetric and anaesthetic complications. Herein, we report the anaesthetic management of a 32-year-old female previously diagnosed with pituitary adenoma and now presenting with twin pregnancy for emergency caesarean section along with emphasis on the anaesthetic concerns pertinent to brain tumours in pregnancy.